Development of the digital environment in ensuring the quality of training of specialists - Karaman, Olena; Moroz, Volodymyr; Bezghynskyi, Yurii; Volodavchyk, Viktoriia; Krutko, Olena (Statistics, Optimization & Information Computing, 2026)
The purpose of the study is to identify key aspects of the development of the digital educational environment and assess its impact on the quality of training of specialists. Special attention is paid to comparing digital platforms, analysing the content of training courses, reviewing the user experience through surveys, and observing the educational process. The methodology included a comparative analysis of popular digital platforms based on the criteria of convenience, integration, functionality, and interaction capabilities. Content analysis of training courses allows assessing the quality of materials, the presence of interactive elements, and the level of content adaptation to the digital environment. The survey, conducted on the basis of the Luhansk Taras Shevchenko National University, includes 180 students and 70 teachers, and monitoring the educational process helped assess the effectiveness of digital technologies in a real educational environment. The main results of the study show that the digital environment contributes to improving the availability of educational materials, personalising training, and automating knowledge assessment. Challenges related to technical difficulties, insufficient digital competence of teachers, and a decrease in the level of live communication are identified. A comparative analysis of the platforms demonstrates that Moodle is the most flexible, while Google Classroom and Microsoft Teams provide higher usability but have limited configurability. Content analysis shows that courses that contain interactive elements (video lectures, simulations, gamification) increase the effectiveness of material assimilation. The results of the study confirm that the digital educational environment has great potential to improve the quality of training of specialists. However, it is necessary to improve the interactive capabilities of the platforms, increase the digital literacy of teachers, and ensure a balance between online and offline interaction. The practical importance of the study is the development of recommendations for educational institutions on the effective implementation of digital technologies, improving the quality of content, and adapting the educational process to modern technological conditions. The results obtained can be used to improve educational policies, develop new digital learning methods, and enhance the effectiveness of educational process management.